DEVELOPING AND PROMOTING THE CULTURE OF INTERGENERATIONAL RELATIONSHIPS WITHIN FAMILY COUNSELORS - Carolina CALARAȘ (Acta et Commentationes, Sciences of Education, 2020)
The article represents a theoretical and applicative study, which addresses the issue of developing and promoting the culture of intergenerational relations in family education, in school education and within the school-family-community partnership through educational counseling. The author elucidates the basic principles, strategies and basic contents of the culture of intergenerational relationship formation in the process of educating family members. Here too are determined the possibilities of developing and promoting the culture of intergenerational relations and the possibilities of the anticipation of difficulties that can arise in the counseling sessions of adults and children.